"I Sleep, but My Heart Waketh": Contiguity between Heinrich Heine's Imago of the Shulamite and Amy Levy's "Borderland". Issue 2 (23rd November 2016) - Devine, Luke
Abstract : "Borderland, " by Amy Levy (1861–89), a refiguring of the Song of Songs' traditional allegory, reverses Song 5:2–6's climax in which the Shulamite unwittingly neglects the advances of her "beloved" while he waits at the door. In "Borderland, " the Shulamite "lover" assumes the initiative by visiting her "beloved, " while he is instead passive. The diverse ways in which "Borderland" can be read reveal contiguity with "Das Hohelied" and "Lyrisches Intermezzo" by German Jewish poet Heinrich Heine (1797–1856), texts also dependent on the Songs of Songs. Indeed, Heine was Levy's "favourite poet"; "Borderland" accordingly reflects her reading of Heine and the employment of similar poetics, though not necessarily continuity or unoriginality. This article therefore looks for what Dan Miron has labelled "literary contiguity, " a process by which "tangible contacts" between "players" in the "modern Jewish literary complex" are identified. This approach identifies "relatedness" between Heine and Levy, but also acknowledges the "differences."